2015
DOI: 10.11604/pamj.2015.21.165.5577
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of otitis externa in Kaduna Nigeria

Abstract: IntroductionOtitis externa (OE) is an inflammation or infection of the external auditory canal (EAC), the auricle, or both this condition has been reported to be found in all age groups. The aims and objectives were, study/determine the prevalence of Otitis externa in the specialist otolaryngology clinic in National Ear Care Center Kaduna, study the pattern of presentation among patients with otitis externa in the specialist otolaryngology clinic in National Ear Care Center Kaduna, and evaluate the choice of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 2 publications
3
12
1
6
Order By: Relevance
“…More recent studies from Jordan and other Middle Eastern Arab countries have shown that P. aeruginosa isolates from clinical specimens were commonly Multidrug Resistant (MDR) to many frequently used antibiotics in clinical medicines such as amikacin, aztreonam, gentamicin, piperacillin-tazobactam and ciprofloxacin, while they were mostly susceptible to imipenem, ceftazidime and colistin B [6 -9]. Many studies have recommended treating patients with colistin B, gentamicin or ciprofloxacin topical preparations as the first-line treatment of otitis externa [2,5,10].…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies from Jordan and other Middle Eastern Arab countries have shown that P. aeruginosa isolates from clinical specimens were commonly Multidrug Resistant (MDR) to many frequently used antibiotics in clinical medicines such as amikacin, aztreonam, gentamicin, piperacillin-tazobactam and ciprofloxacin, while they were mostly susceptible to imipenem, ceftazidime and colistin B [6 -9]. Many studies have recommended treating patients with colistin B, gentamicin or ciprofloxacin topical preparations as the first-line treatment of otitis externa [2,5,10].…”
Section: Introductionmentioning
confidence: 99%
“…This variation in its prevalence is attributable to the large number of patients investigated in contrast to that reported for this study. Pseudomonas sp and Klebsiella sp have also been isolated among patients with otitis externa in a recent study from the same clinic (Musa et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Most cases in northern Nigeria involve prescription of antibiotics empirically to patients with OM in outpatient clinics or patent medicine stores without microbiologic evaluation (Musa et al, Bemu et al, 2015). The National Ear Care Centre Kaduna established to treat cases of OM patients in both rural and urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…Pada studi ini tidak dijelaskan alasan prevalensi laki-laki lebih banyak. 7,8 Perbedaan proporsi berdasarkan jenis kelamin juga dapat dipengaruhi oleh perbandingan jumlah laki-laki dan perempuan pada suatu populasi. Apabila jumlah salah satu jenis kelamin memang jauh lebih banyak pada populasi tersebut, maka memungkinkan proporsi OE berdasarkan jenis kelamin nampak cenderung di dominasi oleh jenis kelamin tersebut.…”
Section: Pembahasanunclassified
“…Kelompok usia ini dikaitkan dengan kebiasaan mereka untuk melakukan pembersihan telinga secara berlebihan dan dengan cara yang lebih kasar dibandingkan dengan kelompok usia lain sehingga menimbulkan peningkatan risiko trauma liang telinga akibat pembersihan telinga. 4,5,8 Gejala klinis tersering adalah nyeri, disusul dengan telinga berair. Hal ini sesuai dengan penelitian Hui yang menemukan bahwa 70% dari penderita OE memiliki keluhan nyeri pada telinga/ otalgia.…”
Section: Pembahasanunclassified